MiR-1236 regulates hypoxia-induced epithelial–mesenchymal transition and cell migration/invasion through repressing SENP1 and HDAC3. Issue 1 (1st August 2016) - Chen, Sung-Yuan; Teng, Shu-Chun; Cheng, Tzu-Hao; Wu, Kou-Juey
Highlights: MiR-1236 represses SENP1 and HDAC3. MiR-1236 is crucial for hypoxia-induced EMT. MiR-1236 is repressed by Twist1. Abstract: Intratumoral hypoxia induces epithelial–mesenchymal transition and promotes cancer metastasis. MicroRNAs (miRNAs) are endogenous, single-strand RNA molecules that regulate gene expression. MiRNAs control cell growth, proliferation, differentiation and cell death and may function as oncogenes or tumor suppressors. HDAC3 and SENP1 are two molecules involved in hypoxia-induced EMT and HIF-1α stability, respectively. In this report, we show that miR-1236 plays a critical role in hypoxia-induced EMT and metastasis. MiRNA prediction programs TargetScan and miRanda show that miR-1236 may target HDAC3 and SENP1. MiR-1236 represses the luciferase activity of reporter constructs containing 3'UTR of HDAC3 and SENP1 as well as the expression levels of HDAC3 and SENP1. MiR-1236 abolishes hypoxia-induced EMT and inhibits migration and invasion activity of tumor cells. Hypoxia represses miR-1236 expression. The promoter region of miR-1236 is identified as the NELFE promoter. Twist1, an EMT regulator activated by hypoxia/HIF-1α, is shown to repress the reporter construct driven by the NELFE promoter. The binding site of Twist1 in the NELFE promoter is identified and chromatin immunoprecipitation assays show the direct binding of Twist1 to this site. Overexpression or knockdown of Twist1 in stable cell lines shows the inverse correlation between Twist1 and miR-1236 expression. These results identify a miRNA that regulates hypoxia-induced EMT and metastasis through repressing HDAC3 and SENP1 expression and present a regulatory network that involves many key players in hypoxia-induced EMT.